2014
DOI: 10.1152/jn.00527.2013
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing activity in the optic tectum is correlated on a trial-by-trial basis with the pupil dilation response

Abstract: Netser S, Dutta A, Gutfreund Y. Ongoing activity in the optic tectum is correlated on a trial-by-trial basis with the pupil dilation response. J Neurophysiol 111: 918 -929, 2014. First published December 4, 2013; doi:10.1152/jn.00527.2013.-The selection of the appropriate stimulus to induce an orienting response is a basic task thought to be partly achieved by tectal circuitry. Here we addressed the relationship between neural activity in the optic tectum (OT) and orienting behavioral responses. We recorded mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
2
2
0
Order By: Relevance
“…NCs evoked by auditory or visual stimulation were measured for 182 and 181 neuronal pairs, respectively. Values ranged from -0.30 to 0.80 (auditory) and -0.22 to 0.93 (visual), a range consistent with a previous report of 14 spontaneously active pairs in owl OT (Netser, Dutta, and Gutfreund 2014). Overall, the mean noise correlation evoked by auditory or visual stimulation was 0.28 and 0.25, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…NCs evoked by auditory or visual stimulation were measured for 182 and 181 neuronal pairs, respectively. Values ranged from -0.30 to 0.80 (auditory) and -0.22 to 0.93 (visual), a range consistent with a previous report of 14 spontaneously active pairs in owl OT (Netser, Dutta, and Gutfreund 2014). Overall, the mean noise correlation evoked by auditory or visual stimulation was 0.28 and 0.25, respectively.…”
Section: Resultssupporting
confidence: 89%
“…Evoked NC values ranged from -0.35 to 0.94, with a mean of 0.28, 0.25, and 0.28 for auditory, visual, and bimodal, respectively. These values are consistent with a prior report of 14 OTd pairs recorded in response to spontaneous activity (Netser, Dutta, and Gutfreund 2014). A recent study using tetrodes in OTd and auditory stimulation reported somewhat lower values, with mean NC values of 0.13 (Beckert, Pavao, and Pena 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, multisensory processing in the SCi (Stein and Meredith, 1993) may also mediate the pupil responses evoked by salient stimuli. Finally, while the robustness of the link between the SCi and salience-evoked pupil dilation remains to be established with recording studies in the monkey, very recent evidence in the owl links aspects of activity in the optic tectum with pupil dilation responses (Netser et al, 2014). Thus, like the neck and shoulder, the SCi has the necessary projections and response properties to modulate salient pupil responses, independent of the OPNs.…”
Section: The Saccadic Burst Generator Is Potently Gated By Omnipause Neuronsmentioning
confidence: 99%
“…Here we took nonverbal sound as a model system to investigate systematically the physiological and behavioral correlates of processing sensory emotional salience in patients with canonical dementia syndromes. We used pupillometry to index autonomic (sympathetic) reactivity: compared with other candidate autonomic indices [36] , [37] , [38] , pupil dilatation responses are relatively resistant to disease-associated movement and other artifacts, well preserved to auditory stimuli in healthy older individuals [39] , track neural responses closely [23] , [40] , [41] , and have social behavioral resonance [42] , [43] . We used affective valence ratings to index the behavioral processing of auditory emotional salience.…”
Section: Introductionmentioning
confidence: 99%